„Non procul ex proprio stipite poma cadunt”, avagy a „két Kolosváry” élete az egyetemtörténet tükrében - Ámán, Ildikó (Gerundium, 2019)
Non procul ex proprio stipite poma cadunt, or the Life of the „two Kolosvárys” in the Mirror of the Univerity History. In my study, I intend to introduce the history of the Faculty. The study outlines the life’s work of father and son, who are closely related to the legal history embedded in the history of the University. They both were closely connected with the city, and in addition to their teaching activities they also played an active role in the social life of Cluj-Napoca: they were chief editors of the papers and presidents of scientific and civil associations. Alexander Kolosváry has played a prominent role in the life of the University and within the Faculty of Law. He was four times the dean of the Faculty and once held the post of rector. In addition, he coproduced the Hungarian translation of Tripartitum and Corpus Juris Hungarici with Professor Clement Óvári. Valentine Kolosváry was considered one of the biggest private lawyers of the century at the time. Valentine Kolosváry was a worthy successor to his father, not only as a head of department at the University but also in the patronage of the Reformed Church of John Calvin and Church Districts and its rights.